Comparison of the calculated absorption and the measured field strength of HF waves reflected from the ionosphere - Aydogdu, M.; Guzel, E.; Yesil, A.; Ozcan, O.; Canyilmaz, M. (Soc Italiana Fisica, 2007)
The absorption (L) of the wave in the ionosphere has been calculated. The 5.47MHz wave is transmitted from Ercis, Turkey (39.03 degrees N, 43.37 degrees E) and received at Elazig, Turkey (38.70 degrees N, 39.20 degrees E). The field strength of this wave is measured by ITU-Compliant HF Field Strength Monitoring Terminal, and the absorption L in the ionosphere has been calculated. It is observed that the field strength of the wave is least around noon time and it increases at night times at all seasons. The diurnal and seasonal variations of the calculated absorption L shows that the maximum absorption in the wave occurs around noon time. The behaviour of the diurnal and seasonal variations of the field strength of the wave can be explained with the diurnal and seasonal variations of the calculated absorption L in the ionosphere. Equation (22) in this paper can be used to obtain the imaginary part (beta) of the refractive index of the ionospheric plasma, and it can be applied to the HF radio waves propagations in the ionosphere for absorption L.
Keywords: Radiowave Absorption